Speech-ABR in contralateral noise: A potential tool to evaluate rostral part of the auditory efferent system. (November 2019) - Lotfi, Yones; Moossavi, Abdollah; Javanbakht, Mohanna; Faghih Zadeh, Soghrat
Abstract: In parallel with the auditory afferent system, the auditory efferent system is active in all parts of the auditory pathways from auditory cortex to the cochlea. The auditory efferent system has two main segments: the rostral and the caudal parts. The rostral part, which starts from the cortical centers to thalamic nuclei and continues into collicular pathways in rostral brainstem, which sends its neural fibers to the main collicular nuclei especially inferior colliculus. The caudal part includes the olivocochlear bundle, which originates from the superior olivary complex and terminates on the cochlear hair cells. Most studies about the auditory efferent system have focused only on the caudal part using otoacoustic emission suppression test. Speech-evoked auditory brainstem response (S-ABR) as an electrophysiologic test that uses speech stimuli to simulate real-life auditory conditions, reflects the performance of rostral brainstem centers, so structurally seems to be an appropriate candidate to examine the rostral part of the auditory efferent system. Our hypothesis is that S-ABR in noisy condition, a typical condition for stimulating the auditory efferent system, has the potential to be used as an objective noninvasive electrophysiologic test for studying the rostral auditory efferent system in diagnosis and treatment/rehabilitation follow-ups. In addition, S-ABR can potentially reflect higher-order auditory functions and the effects of their dysfunctions on the lower brainstem. This characteristic makes S-ABR even more suitable tool for evaluation of the efferent system. To evaluate our hypothesis, Eighteen normal hearing subjects in the age range of 18–25 were tested in a pilot study for S-ABR in quiet mode and three signal to noise ratios of +10, 0 and −10 for both ears. Then we checked the correlation between the results of S-ABR in different conditions and scores of auditory behavioral tests that auditory efferent system is involved in them: Consonant-Vowel perception in noise, dichotic Consonant-Vowel-Consonant and sound lateralization in noise. The results of our pilot study showed a significant correlation between S-ABR changes in noise with the scores of the behavioral tests in noisy or dichotic situations. Findings of the current study suggest that S-ABR with specific contralateral noise can be an appropriate option for evaluating the performance of rostral part of the auditory efferent system and may be suitable for top-down auditory training follow-ups, although the generalization of these results needs further studies in different groups with different auditory processing abnormalities or skills.